2014
DOI: 10.1021/ml400422a
|View full text |Cite
|
Sign up to set email alerts
|

Iron Chelators in Photodynamic Therapy Revisited: Synergistic Effect by Novel Highly Active Thiosemicarbazones

Abstract: In photodynamic therapy (PDT), a noninvasive anticancer treatment, visible light, is used as a magic bullet selectively destroying cancer cells by a photosensitizer that is nontoxic in the dark. Protoporphyrin IX (PpIX) is a natural photosensitizer synthesized in the cell, which is also a chelating agent that if bonded to Fe 2+ forms heme, a central component of hemoglobin. Therefore, xenobiotic iron chelators can disturb iron homeostasis, increasing the accumulation of PpIX, obstructing the last step of heme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…An example of such compounds are bispyridine iron chelators that have been widely investigated for anticancer activity. [27][28][29][30][31] Chelating metal ions as a mechanism of action may increase selectivity as cancer cells often have a higher level of biologically relevant metal as iron, copper, and zinc. In this regards, iron and especially copper for its ability to generate reactive oxygen species seems to be valuable.…”
Section: Biological Studiesmentioning
confidence: 99%
“…An example of such compounds are bispyridine iron chelators that have been widely investigated for anticancer activity. [27][28][29][30][31] Chelating metal ions as a mechanism of action may increase selectivity as cancer cells often have a higher level of biologically relevant metal as iron, copper, and zinc. In this regards, iron and especially copper for its ability to generate reactive oxygen species seems to be valuable.…”
Section: Biological Studiesmentioning
confidence: 99%
“…Thiosemicarbazones (TSCs) are sulfur-containing organic substances whose biological properties have been extensively studied [1][2][3][4][5][6][7][8], in particular their activities against microbial diseases as malaria, small-pot, influenza, leishmaniasis or chagas [9][10][11][12][13][14], neurological pathologies [15,16] and cancer [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Different biological targets have been identified, like DNA [37][38][39], RNA [40] and several enzymes as RNA-dependent DNA polymerases [41], xanthine oxidoreductase [42], thioredoxin reductase [43,44], topoisomerase IIa [45][46][47] or s...…”
Section: -Introductionmentioning
confidence: 99%
“…Finally, Mrozek-Wilczkiewicz et al 72 have reported the concept of enhancing ALA-PDT using thiosemicarbazone (TSC) iron chelators, which have been previously developed as standalone anticancer agents (Fig. 13).…”
Section: Modulators Of the Heme Pathway: Iron Chelatorsmentioning
confidence: 99%